Identifikasi Peran Pemangku Kepentingan dalam Pengembangan UMKM Berbasis Lahan Gambut untuk Pembangunan Berkelanjutan: Pendekatan Prospektif dengan Mactor di Kota Palangka Raya: Identifying Stakeholder Roles in the Development of Peatland-Based MSMEs for Sustainable Development: A Prospective Analysis Using Mactor in Palangka Raya City - Raysharie, Puput Iswandyah; Alexandro, Rinto; Setyowati, Erni Dwi Puji; Santoso, Yonatan Ari (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Peatlands play a crucial role in supporting human life, storing carbon, and maintaining environmental balance. Their economic potential, through peat-based products such as charcoal, rattan, and medicinal plants, is significant. However, their utilization is constrained by market access, funding, and technology. The objective of this study is to examine the role that stakeholders play in the establishment of MSMEs based on the data in the city of Palangka Raya. The research employs a mixed-method approach with prospective analysis using Mactor software. Data was gathered through in-depth interviews and field observations. The findings show that the Regional National Craft Council (Dekranasda), financial institutions, MSME actors, and the Trade Department play strategic roles, while WWF focuses on environmental preservation. Challenges such as inter-actor dependency and a lack of effective collaboration need to be addressed. This study recommends optimizing collaboration, policy support, as well as the incorporation of economic and environmental goals to support the sustainability of peat-based MSMEs.